The Contribution of Authoritative Parenting Style to Entrepreneurial Preparedness: Mediated by Risk Tolerance, Self-Efficacy, and Creativity - Tiara Nur Anisah; Andika, Andika; Eni Andari; Nadia (Dinasti Publisher, 2023)
This study aims to investigate the relationship between authoritative parenting and entrepreneurial preparedness, with risk tolerance, self-efficacy, and creativity as mediating factors. Parenting styles play a significant role in shaping children's behavior, including nurturing their entrepreneurial spirit from an early age. The study involved a sample of 296 respondents. IBM AMOS version 23 was employed for hypothesis testing. Additionally, a sobel-test calculator was utilized to examine mediation. Ultimately, the results support all nine proposed hypotheses, providing valuable insights into the relationship between authoritative parenting, risk tolerance, self-efficacy, creativity, and entrepreneurial preparedness. The findings confirm several key aspects that researchers initially hypothesized. First, authoritative parenting has a positive and significant impact on risk tolerance, self-efficacy, and creativity. Second, risk tolerance, self-efficacy, and creativity have positive and significant effects on entrepreneurial preparedness. Furthermore, the results indicate that risk tolerance, self-efficacy, and creativity mediate the relationship between authoritative parenting and entrepreneurial preparedness. The findings of this research demonstrate that authoritative parenting can influence children's character development, leading to higher levels of creativity, self-confidence, and risk tolerance traits essential for entrepreneurs